Intrapancreatic Accessory Spleen Mimicking Neuroendocrine Tumor on 68Ga-DOTATATE PET/CT. (September 2015) - Bhure, Ujwal; Metzger, Jürg; Keller, Franziska Aebersold; Zander, Andrea; Lago, Marisol Pérez; Herring, Kerstin; Strobel, Klaus
<x xml:space="preserve">Abstract</x> Abstract Besides well-known physiologic uptake of 68Ga-DOTATATE in spleen, pituitary gland, pancreatic head, adrenals, kidney, and urinary bladder, sometimes unusual areas of uptake are found. We report a case of a 53-year-old woman who had vague pain in abdomen for which abdominal CT was done showing a contrast-enhancing lesion in the pancreatic tail. It was suspected to be of neuroendocrine origin and 68Ga-DOTATATE PET/CT showed a corresponding focal uptake. Spleen-preserving pancreatic tail resection was performed. Pathology revealed the diagnosis of an accessory intrapancreatic spleen (AIPS).